Socio-Economic Profile and Knowledge Level of Dairy Farmers about Improved Dairy Farming Practices in Jammu District - Shazia Shafiq; Pranav Kumar; S.A.Khandi; M.S.Bhadwal (Journal of Agricultural Extension Management, 2013)
The present investigation was conducted in Jammu district of J & K state wit!· the objective to assess the knowledge level of dairy farmers about improved dairy farming practices. The data were collected from 120 respondents, belonging to R.S Pura and Marh block, through personal interview. The study revealed that a majority of the respondents were in the middle age group and majority had poor education. The respondents were mainly marginal farmers with land holding of less than 2.5 acres and a herd size of 2-4 animals. Most of the dairy farmers had low level of social participation and extension contact. However, they had medium level of mass media exposure. The study revealed that majority of the respondents (71.66%) had medium level of knowledge about improved dairy farming practices. The dairy farmers had greater knowledge about feeding practices (73.28%) and least about improved breeding practices (48.22 %). It is suggested that efforts may be made to increase the literacy rate of farmers so that they can utilize the available literature for improving their knowledge as well as skills. Mass media also need to be utilized for transfer of improved dairy farming practices to farmers for enriching their knowledge